The Influence of Public Goods on the Development of China’s Regional Economy – A Spatial Econometric Approach - Li, Jialin (European Scientific Journal, ESJ, 2018)
China’s economy has been soaring in the recent decades. Nevertheless, it is characterized by problems of imbalance of economic development, which could hinder the sustainable development of the economy. This paper selects data of various kinds of public goods provision and regional economic development status in China from 2007 to 2014, and investigates the influence of public goods on the development of China’s regional economy from using a spatial econometric approach. Empirical findings show that there is a significant spatial correlation within the data of public goods investment during 2007 and 2014, and that the investment on public goods has positive influence on development of regional economy. The finding also shows that there exist spatial spillover effects, which means that the investment in regional public goods can boost the economic growth of surrounding regions.